Underweight and its associated factors among reproductive age women on antiretroviral therapy in selected public health facilities of Arsi Zone, South East Ethiopia - Sufedin Ibrahim; Takele Gezahegn Demie; Temesgen Gelata; Seifadin Ahmed; Gemechu Gelan Bekele (Clinical Epidemiology and Global Health)
Background: Despite progress in HIV treatment, the reproductive age group continues to experience high rates of underweight, which adversely affects their health and ART effectiveness. Current data on the prevalence and contributing factors of underweight in this group is scarce. This study aims to assess the prevalence of underweight and its associated factors among reproductive-age women on ART in selected public health facilities in the Arsi Zone, South East Ethiopia. Methods: A health facility-based cross-sectional study was conducted involving 413 individuals receiving ART between December 15, 2021, and January 20, 2022. Data were collected through a review of medical records and interviews with selected participants. Bivariate and multivariable logistic regression analyses were used to identify factors associated with underweight among this population. Results: This study found that the prevalence of underweight among women on ART was 24.5 % (95 % CI: 20.8%–28.3 %). Underweight was significantly associated with ambulatory status (individuals who can perform selfcare but can't fully engage in work) (AOR = 4.41, 95 % CI: 1.71–11.36), lack of HIV/AIDS-related nutrition counselling (AOR = 4.61, 95 % CI: 2.17–9.78), poor ART adherence (AOR = 11.49, 95 % CI: 4.77–27.67), and inadequate dietary diversity (AOR = 3.84, 95 % CI: 1.82–8.11). Conclusion and recommendation: The study revealed a high prevalence of underweight among women on ART. To effectively tackle this issue, enhancing nutritional counselling, strengthening ART adherence programs, and promoting a diverse diet are essential. Moreover, providing targeted support for ambulatory patients can further mitigate underweight in this group. By implementing these recommendations, we can improve health outcomes for women living with HIV/AIDS.